Parametric investigations of drying callophyllum inophyllum fruit for the oil extraction process - Tan, Chee Wang; Amiril Sahab, Abdul Sani; Zubaidah, Zamri (Penerbit UMP, 2023)
Lubricant is a chemical that reduce the friction. Lubricant is made of petroleum, this petroleum-based lubricant is dangerous, It will affect the ecology system. The demand of lubricant is kept increasing but the petroleum is decreasing over the years. The alternative way needs to find out. One of the alternative way is bio-lubricant. Bio-lubricant can be biodegradable by the bacteria and no pollution. Callophyllum inophyllum (CI) can be one of the ingredient to manufacture bio-lubricant because it has higher oil yield. To extract the oil of CI, drying process is necessary to carry out. In this project, a dryer is built to investigate the best parameter to dry CI and also find out which parameter is the most suitable to dry CI through the experiment. Drying curve is plotted to provide more understanding for the behaviour of drying of Calophyllum Inophyllum Fruits. Furthermore, the quantity of heat and the latent heat of vaporization were calculated to determined how much heat were needed to raise temperature and vaporize the moisture content inside callophyllum inophyllum.